2012
DOI: 10.1589/jpts.24.1063
|View full text |Cite
|
Sign up to set email alerts
|

What Kinds of Impressions Did Physical Therapy Students Receive through Participation in Off-campus Classes? - An Analysis Using Text-mining

Abstract: Abstract.[Purpose] A community-based education program has been conducted since 2009 at The School of Health Sciences, Gunma University. This study investigated how the off-campus program affected physical therapy students using text analysis methods.[Methods] The subjects were 60 physical therapy students, who participated in the off-campus classes. Each student submitted a self-assessment worksheet after participation. Using text analysis methods, the 60 worksheets were broken down into words. The extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These items are characterized as active learning behavior at school. Previous research has found that student-centered rather than faculty-centered learning motivates physical therapy students, and that they regard self-directed learning as important 7 , 8 ) . The result of this study indicates that self-directed learning may be influenced by the motive to become a physical therapist before admission.…”
Section: Discussionmentioning
confidence: 99%
“…These items are characterized as active learning behavior at school. Previous research has found that student-centered rather than faculty-centered learning motivates physical therapy students, and that they regard self-directed learning as important 7 , 8 ) . The result of this study indicates that self-directed learning may be influenced by the motive to become a physical therapist before admission.…”
Section: Discussionmentioning
confidence: 99%
“…The third page of the repository application groups “similar” papers into clusters. A clustering algorithm involving “Euclidean” distance between words across the literature is implemented across the selection of abstracts and group papers into three clusters ( Nakagawa et al, 2012 ). This technique allows the user to further sub-select the papers into similar clusters, potentially enabling more intentional digestion of information.…”
Section: Methodsmentioning
confidence: 99%
“…The text mining approach has been used with various types of qualitative data, such as written records by nurses during disasters, 5 interview data related to multidisciplinary cooperation among medical professionals 6 and free-response content in class assessment surveys. 7 If the text mining approach is applied to the records of the preventive care programme, other effects, which are difficult to evaluate by an objective numerical value, may become obvious. In addition, by investigating the frequency of occurrence of words, it may be possible to obtain new insights into these programmes.…”
Section: Backg Rou N Dmentioning
confidence: 99%